2019
DOI: 10.1111/aogs.13547
|View full text |Cite
|
Sign up to set email alerts
|

Management and treatment of cervical intraepithelial neoplasia in the Netherlands after referral for colposcopy

Abstract: Introduction The aim of this study was to describe trends in the diagnosis and treatment of women referred from the national screening program with cervical intraepithelial neoplasia (CIN) in the Netherlands, and to compare these trends with national guidelines and identify potential areas for improvement for the new primary high‐risk HPV screening program. Material and methods We conducted a population‐based cohort study using data from the Dutch pathology archive. Women aged 29‐63 years who took part in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…This is in line with the Dutch guidelines, advising conservative management in women with CIN2 and who have not yet completed childbearing, which had been implemented in 2015. 9,23 The rate of histologic results indicating CIN1 increased to 143.4%, and women were managed conservatively after biopsy nearly 2.5 times more often in hrHPV-based screening than in cytology-based screening (1745 vs 696 per 100,000 screened women, respectively). The Dutch study from Aitken et al 20 revealed 2.2 times more CIN1 in hrHPV-based screening; however, they did not further differentiate between overdiagnosis or overtreatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the Dutch guidelines, advising conservative management in women with CIN2 and who have not yet completed childbearing, which had been implemented in 2015. 9,23 The rate of histologic results indicating CIN1 increased to 143.4%, and women were managed conservatively after biopsy nearly 2.5 times more often in hrHPV-based screening than in cytology-based screening (1745 vs 696 per 100,000 screened women, respectively). The Dutch study from Aitken et al 20 revealed 2.2 times more CIN1 in hrHPV-based screening; however, they did not further differentiate between overdiagnosis or overtreatment.…”
Section: Discussionmentioning
confidence: 99%
“…7 In one study, managements were given among CIN I patients expectant management 34.6%, local ablative methods 7.3% & LEEP 56.8% cases, whereas in this study, expectant treatment were received 25(33.3%), 53.3% were treated with either cold coagulation or other ablative method & 13.3% LEEP regarding their size & extent of lesions.8 Excision procedure done in this study were in 13.3% cases, where as in other study it was about 26.4%. 9 Persistence of disease were found in 2(13.3%) ladies those did not receive treatment & came for follow up within 12 months, 3(10.7%) who were treated with cold coagulation & 1(12.5%) lady who received treatment with LEEP in this study, whereas persistence & progression of disease in case of immediate treatment about 1.7% & 4.4% in non treatment group in another study, which are much lower than this study. 10 There is very little difference in the frequency of colposcopic abnormalities during the follow up period between 3 treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of colposcopy practice in U.S. community‐based clinics found 87.2% of the patients as having low‐grade indications, namely atypical squamous cells of undetermined significance (ASCUS)/LSIL/HPV positive; additionally 13% of the patients were <25 years 9 . A nationwide study from the Netherlands reported that despite guidelines recommending not to treat, 26.4% of CIN1 lesions were treated with large excisions 16 . Maura et al 17 found 10% of almost 6 million French women who underwent a Pap smear to be <25 years old, although national guidelines recommended initiating screening from the age of 25 years.…”
Section: Introductionmentioning
confidence: 99%